Giant basal cell carcinoma of the breast mimicking Paget's disease: Complete remission after photodynamic therapy - Mikhaimer, Nadia C.; Kaehler, Katharina C.; Schwarz, Thomas; Mundhenke, Christoph; Hauschild, Axel (Onkologie, 2010)
Background: Basal cell carcinoma (BCC) in the nipple area is extremely rare and can be mistaken for Paget's disease. Case Report: A 47-year-old woman complained of a slowly growing, scaly erythematous plaque around her right nipple which had developed over several years. Paget's disease of the breast was suspected. Biopsies revealed a superficial BCC. The maximum tumor thickness was measured as 1 mm. Considering the superficial character of the tumor, photodynamic therapy (PDT) as a non-invasive approach was performed. Complete remission (CR) with an excellent cosmetic result was achieved after 4 PDT sessions. In the follow-up, CR with no signs of a local recurrence was evident after more than 24 months. Conclusion: In similar superficial cases of BCCs, non-invasive procedures such as PDT can be discussed as an alternative option to radical surgery or radiotherapy, with an excellent aesthetic outcome in carefully selected cases. Copyright © 2010 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2022-11-17
Keywords: 5-Aminolevulinic acid; Basal cell carcinoma; Breast; Paget's disease; Photodynamic therapy